Construction of a New Class of Tetracycline Lead Structures with Potent Antibacterial Activity through Biosynthetic Engineering. Issue 13 (4th February 2015) - Lešnik, Urška; Lukežič, Tadeja; Podgoršek, Ajda; Horvat, Jaka; Polak, Tomaž; Šala, Martin; Jenko, Branko; Harmrolfs, Kirsten; Ocampo‐Sosa, Alain; Martínez‐Martínez, Luis; Herron, Paul R.; Fujs, Štefan; et al.
Abstract Antimicrobial resistance and the shortage of novel antibiotics have led to an urgent need for new antibacterial drug leads. Several existing natural product scaffolds (including chelocardins) have not been developed because their suboptimal pharmacological properties could not be addressed at the time. It is demonstrated here that reviving such compounds through the application of biosynthetic engineering can deliver novel drug candidates. Through a rational approach, the carboxamido moiety of tetracyclines (an important structural feature for their bioactivity) was introduced into the chelocardins, which are atypical tetracyclines with an unknown mode of action. A broad‐spectrum antibiotic lead was generated with significantly improved activity, including against all Gram‐negative pathogens of the ESKAPE panel. Since the lead structure is also amenable to further chemical modification, it is a platform for further development through medicinal chemistry and genetic engineering.